Aristolochia baetica L. (Aristolochiaceae): New Records of Rare Medicinal Species from Northwestern Algeria - Mansouri Lahouaria Mounia; Kheloufi Abdenour; Boukhecha Mohamed (Contemporary Agriculture, 2022)
Based on vegetation surveys made in 2020 and 2021, the present paper reports the first records of Andalusian pipevine - Aristolochia baetica L. (Aristolochiaceae) in Oran (northwestern Algeria). This species has been previously recorded only in Sidi Bel Abbès and Tlemcen (Algeria). Therefore, this statement can be considered as an addition to the flora of Algeria. The species was found in 10 out of 26 municipalities from the city of Oran. A distribution map of these new records is included. The paper describes its reproduction, ecology, and phenology. Photographs of different plant organs at different seasons of the year are also provided for this poorly known species. The recorded populations were very small in size (<3 populations per municipality) and in the number of individuals (<5 ind.). Conservation efforts may be necessary to protect and increase the population size of this species.